2017
DOI: 10.13075/ijomeh.1896.00841
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of fungi and cytotoxicity of the species: Aspergillus ochraceus, Aspergillus niger and Aspergillus flavus isolated from the air of hospital wards

Abstract: Objectives: The basic care requirement for patients with weakened immune systems is to create the environment where the risk of mycosis is reduced to a minimum. Material and Methods: Between 2007 and 2013 air samples were collected from various wards of a number of hospitals in Kraków, Poland, by means of the collision method using MAS-100 Iso MH Microbial Air Sampler (Merck Millipore, Germany). The air mycobiota contained several species of fungi, and almost 1/3 of it was made up of the species of the Aspergi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Also in the authors' own study, moulds belonging to Aspergillus genus made up a significant percentage of the identified fungi, including A. fumigatus, which was observed in over a half of the isolates of this type. The fungi belonging to Aspergillus genus might present a significant threat to patients' health, especially those with impaired immunity, and particularly newborns [28,29,30]. They may also pose a threat to the staff working in these rooms because they are included in the group of 2 biological factors which may have negative effects on people exposed to them for prolonged periods [31].…”
Section: Discussionmentioning
confidence: 99%
“…Also in the authors' own study, moulds belonging to Aspergillus genus made up a significant percentage of the identified fungi, including A. fumigatus, which was observed in over a half of the isolates of this type. The fungi belonging to Aspergillus genus might present a significant threat to patients' health, especially those with impaired immunity, and particularly newborns [28,29,30]. They may also pose a threat to the staff working in these rooms because they are included in the group of 2 biological factors which may have negative effects on people exposed to them for prolonged periods [31].…”
Section: Discussionmentioning
confidence: 99%
“…Open Petri dishes were exposed to air for between 10 and 30 min at a height of 80 to 150 cm from the floor. However, most authors employed air vacuum devices such as Anderson single-step model (10-710), MAS 100 Iso MH Microbial Air Sampler (Merck Millipore, Germany), SAS SUPER 100 (Merck), and LWC (Kangjie Instrument Research Institute, Liaoyang, China) at a variable flow rate (28.3-100 L/min) to obtain the suspended particle concentration (Martins-Diniz et al, 2005;Krajewska-Kułak et al, 2007;Chuaybamroong et al, 2008;Quadros et al, 2009;Ortiz et al, 2009;Qudiesat et al, 2009;Gniadek et al, 2010;Kim et al, 2010;Boff et al, 2013;Macedo et al, 2013;Park et al, 2013;Hoseinzadeh et al, 2013;El-Sharkawy & Noweir, 2014;Maldonado-Vega et al, 2014;Yu et al, 2015;Gniadek et al, 2017;Abbasi & Samaei, 2019). In some studies, material from inanimate surfaces (keyboards, phones, stethoscope, beds, door handles, walls, and equipment) was also collected by means of swabs or imprints (Martins-Diniz et al, 2005;Krajewska-Kułak et al, 2007;Melo et al, 2009;Qudiesat et al, 2009;Sales et al, 2011;Aboul-Nasr et al, 2014).…”
Section: Collection and Cultivation Techniquesmentioning
confidence: 99%
“…Regarding fungi, Aspergillus fumigatus is one of the most studied species in clinical environments due to their high prevalence as contaminants in clinical material, while being responsible for invasive fungal infections among immunocompromised patients [24]. Their great toxicity is due to the production of specific mycotoxins, such as aflatoxin B1, ochratoxin A, and gliotoxin.…”
Section: Introductionmentioning
confidence: 99%